Vertical Paper Analytical Devices Fabricated Using the Principles of Quilling and Kirigami - Bingbing Gao (Nature Portfolio, 2017)
Abstract Here we report the vertical paper analytical devices (vPADs) fabricated using the principles of quilling and kirigami. What differentiates the vPADs from conventional paper microfluidic devices is that the paper substrate used to fabricate the device is placed vertically to the device plane. The fabrication of vPADs with high precision is instrument-free, requiring no photolithography, printing or heating. Two- and three-dimensional vPADs are fabricated for multiplex colorimetric assays of four biochemical indicators and automated enzyme-linked immunosorbent assay of human myoglobin, respectively.